Desenvolvimento e avaliação de recurso educacional multimídia sobre fototerapia para orientação da família - Negré, Glaucia Regina Lopes (2011)
Hyperbilirubinemia or jaundice is the result of overproduction or decreased excretion of bilirubin, this process can occur in newborns high or low risk. This disorder causes the appearance of a yellowish skin and sclera, and phototherapy the most common choice for treatment. The installation of phototherapy is part of routine care in hospitals, but for parents of newborns diagnosed with jaundice, this experience can be traumatic moment is central health education aimed at communication between nursing staff and parents procedures to which the newborn will be submitted. This study aims to develop and evaluate a multimedia educational resource on phototherapy guidelines for parents of newborns who will submitted to phototherapy to treat jaundice. This is an applied research that resulted in a multimedia educational resource entitled Phototherapy Orientations for the Family, which demonstrates the procedures necessary for the effectiveness of the treatment of jaundice. It is hoped that the results may support proposals for interventions and new research to assess the educational resource development.